Analysis of Smart Tank Clean Water Supply Infrastructure Development - Waluyo, Shiddiq; Purwanto, M Yanuar J; Pramudya, Bambang; Rustiadi, Ernan; Hasan, Moh (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to develop an appropriate clean water supply infrastructure, to increase the need for clean water infrastructure, especially smart tanks following the development of the city and society. Quantitative descriptive analysis is used to identify the existing clean water supply infrastructure. The results of quantitative descriptive analysis show that the existing service area of the Piping SPAM Cibinong urban settlement area is an area that is used as the center of urban activities with an existing service level of 17.26%. The existing raw water source used by PDAM Cibinong District is the Ciliwung River with a water discharge rate of 643.360 l/sec. PDAM Tirta Kahuripan in 2018 was only able to produce clean water of 643,360 l/second, so that there was a shortage of clean water in Cibinong sub-district in 2038 of 748 l/second, therefore we had to look for alternative sources of raw water. To be able to realize the fulfillment of clean water supply infrastructure in urban areas precisely in accordance with urban development, the construction of a water supply system is immediately carried out by developing clean water supply infrastructure, in this case the smart tank design. The development of clean water supply infrastructure is expected to be able to overcome the shortage of water supply infrastructure and clean water.